Fatigue and alcohol consumption in heavy truck drivers - García-Perales, Laura Alicia (Universidad de Sonora, 2023)
Introduction: Fatigue, a feeling integrated by physical, mental and neurosensorial symptoms of exhaustion, tiredness and lack of energy, can be a conditioning factor that increases the vulnerability of the working population to acquire harmful behaviors such as alcohol consumption, especially in heavy truck drivers. Objective: To identify the relationship between fatigue and alcohol consumption in heavy truck drivers in Nuevo Laredo, northern border of Mexico. Methodology: Cross-sectional study, with descriptive-correlational design, in a sample of 224 drivers selected by non-probabilistic sampling. Participants who were active at work and who drove fifth-wheel trucks were included, and those who did not complete the questionnaires were excluded. A Sociodemographic Data Questionnaire, the Subjective Symptoms of Fatigue Test and the AUDIT Test were applied. The confidentiality and anonymity of the participants was guaranteed. The data were processed using the SPSS statistical package version 24.0, by means of nonparametric inferential analysis. Results: Drivers with low fatigue 87.1% prevailed, and those with risky consumption, that is, 58.0%, which were followed by dependent consumption, that is, 23.2%. A statistically significant positive relationship was identified between driver fatigue and alcohol consumption with rs = .230, p = .001. Conclusions: The findings indicate that the greater the fatigue, the greater the alcohol consumption in heavy truck drivers, which highlights the need for the design and implementation of effective and timely nursing interventions that contribute to reduce health risk behaviors.